A comparative reading of the Elijah Cycle and its implications for Deuteronomistic ideology - Prinsloo, G.T.M. (Gert Thomas Marthinus) (University of Pretoria, 2018)
Dissertation (MA (Ancient Languages and Cultures))--University of Pretoria, 2005.